Effect of cyanobacteria on growth and yield of boro rice under different levels of urea - Khatun, Wahida; Ud-Deen, Md. Musleh; Kabir, Golam (Rajshahi University Journal of Life & Earth and Agricultural Sciences, 2015)
A pot culture and a field experiment were conducted with cyanobacteria in presence and absence of different levels of urea to evaluate their effects on growth and yield of rice cv. BRRI Dhan 28, 29 and 36 during Boro season of 2007. The treatments were T1 (control), T2 (only cyanobacteria), T3 (recommended doses of urea - 60 kg N/ha), T4 (45% recommended doses of urea + cyanobacteria), T5 (65% recommended doses of urea + cyanobacteria) and T6 (85% recommended doses of urea + cyanobacteria). The maximum values for different growth, yield and yield components (plant height, number of productive tillers/hill, panicle length, number of grains/panicle, 1000-grain weight, and grain, straw and biological yield) were observed in BRRI Dhan 29 under T6 (85% recommended doses of urea + cyanobacteria) and lowest was observed in BRRI Dhan 28 under T1 (neither urea nor cyanobacteria). Uses of cyanobacteria increased the yield of Boro rice varieties and decreased the use of urea by 15-20%.